UVA & UVB-INDUCED SKIN AGEING : Causes and Prevention - Muhammad Wahizul Haswan, Abdul Aziz (UNIMAS Publisher, 2025)
As we get older, our skin naturally ages, but spending too much time in the sun can make it happen faster. The sun's ultraviolet (UV) rays are the main culprit. There are two types: UVA and UVB. UVA rays go deep into the skin and cause long-term damage, while UVB rays mainly affect the surface, causing sunburn and even harming skin cells' DNA. When the sun speeds up skin ageing, it’s called photoageing.